Parameter selection for nonnegative l1 matrix/tensor sparse decomposition - Wang, Y.; Liu, Wan-Quan; Caccetta, Louis; Zhou, Guanglu (Elsevier, 2015)
For the nonnegative l1 matrix/tensor sparse decomposition problem, we derive a threshold bound for the parameters beyond which all the decomposition factors are zero. The obtained result provides a guideline on selection for l1 regularization parameters and extends the corresponding result on Lasso optimization problem.